1998
DOI: 10.4319/lo.1998.43.5.0896
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar polysaccharides in marine macromolecular organic matter as imaged by atomic force microscopy and transmission electron microscopy

Abstract: A consensus is now emerging that the structure of organic macromolecules will determine their function in aquatic systems. Transmission electron microscopy (TEM) is a widely used technique to study the morphology of biomolecules that, under the proper conditions, allows for accurate determination of the shapes and horizontal dimensions of macromolecules. Atomic force microscopy (AFM) is a newe: technique that has better overall resolution, particularly on the vertical scale. Although careful controls must be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
151
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 37 publications
13
151
0
4
Order By: Relevance
“…All previous measurements made on operationally defined "carbohydrate-like" fractions of HMWDOC show this fraction to be significantly depleted relative to DIC Δ 14 C, consistent with slow cycling and turnover times of several decades (Santschi et al, 1998, Loh et al 2004. Using the compound specific approach we find carbohydrates to have radiocarbon values equal to or at most only slightly depleted from DIC, consistent with rapid cycling on annual rather than decadal time scales (see next section).…”
Section: Hmwdommentioning
confidence: 53%
See 1 more Smart Citation
“…All previous measurements made on operationally defined "carbohydrate-like" fractions of HMWDOC show this fraction to be significantly depleted relative to DIC Δ 14 C, consistent with slow cycling and turnover times of several decades (Santschi et al, 1998, Loh et al 2004. Using the compound specific approach we find carbohydrates to have radiocarbon values equal to or at most only slightly depleted from DIC, consistent with rapid cycling on annual rather than decadal time scales (see next section).…”
Section: Hmwdommentioning
confidence: 53%
“…Therefore, in order to obtain an estimate of semi-reactive DOC residence time without interference from the recalcitrant DOC fraction, several recent studies have reported radiocarbon measurements of carbohydrate fractions isolated from high molecular weight dissolved organic matter (HMWDOM). Santschi et al (1998) carbohydrates (> several decades). However, as carbohydrates were not directly identified or quantified in fractions that were analyzed for radiocarbon, the relative depletion in Δ 14 C observed in both studies could be due to the inclusion of radiocarbon depleted, non-carbohydrate impurities in the carbohydrate-like fraction.…”
mentioning
confidence: 99%
“…Confirmation of such a colloid trap model come from the AFM and TEM results (Santschi et al, 1998, Wilkinson et al, 1999, which show abundant fibrils covered by smaller spherical colloids. Colloid trapping by mineral particles appears to be responsible also for the observed enhancement of the Kd value for Pu(IV) onto mineral particles such as silica, as compared to the linear sum of the individual Kd values (e.g., calculated from silica and EPS as end-members).…”
mentioning
confidence: 88%
“…They can constitute a significant proportion of freshwater NOM, varying seasonally between ca. 5-30% in the surface waters of lakes (Figure 4; Leenheer 2000)) and often accounting for an even larger proportion of the NOM in the surface waters of marine systems (Aluwihare et al 1997;McCarthy et al 1998;Santschi et al 1998). In marine systems, fibrillar polysaccharides have been shown to be refractory enough to be found in the deep ocean where they may have lifetimes of hundreds of years (Guo and Santschi 1997) while peptidoglycans appear to be degraded much faster (turnover time of weeks to months; (Nagata et al 2003)).…”
Section: Autochthonous Macromolecules: Proteins Lipids and Polysacchmentioning
confidence: 99%
“…Fig. 4 ; (Santschi et al 1998;Wilkinson et al 1999)) show that their total length may be larger than 1 µm, whereas their thickness is often only a few nm. Furthermore, because they are often charged molecules (i.e.…”
Section: Autochthonous Macromolecules: Proteins Lipids and Polysacchmentioning
confidence: 99%